Orthostatic hypertension is associated with lower plasma Aβ42/Aβ40 ratio: The Multidomain Alzheimer Preventive Trial (MAPT). (31st December 2021) - Rouch, Laure; Rolland, Yves; Hanon, Olivier; Vidal, Jean‐Sébastien; Andrieu, Sandrine; Barreto, Philipe de Souto; Vellas, Bruno
Abstract: Background: Orthostatic hypertension (OHYPER), an emerging hemodynamic cardiovascular risk factor, is associated with cardiovascular events and mortality. Recent findings indicated that it could be an important risk factor for cognitive decline and dementia, including Alzheimer's disease (AD). We aimed to assess the association between OHYPER and low plasma Aβ42 /Aβ40 ratio, a surrogate biomarker for brain amyloidosis, associated with greater risk of mild cognitive impairment (MCI) and AD. Method: We included 483 non‐demented community‐dwelling participants aged ≥ 70 years from the Multidomain Alzheimer Preventive Trial (MAPT). OHYPER was assessed at baseline and defined as an increase of at least 20 mmHg in systolic blood pressure (BP) and/or 10 mmHg in diastolic BP after standing. Plasma Aβ42 and Aβ40 were measured at 12 months, using an immunoprecipitation and liquid chromatography‐mass spectrometry assay. Low plasma Aβ42 /Aβ40 ratio was defined as ≤ 0.107. Logistic regression models were used to assess the association between OHYPER and low plasma Aβ42 /Aβ40 ratio. Result: Of 483 participants (mean age 76 years, 59% female), 113 (23.6%) had OHYPER and 161 (33.3%) low plasma Aβ42 /Aβ40 ratio. OHYPER was associated with low plasma Aβ42 /Aβ40 ratio (OR = 1.58, 95% CI [1.02‐2.44]) in unadjusted models. Adjustment for age, sex, education, MAPT randomization group, lying BP, antihypertensive drug use, MCI, and presence of 1 or 2 ApoE ε4 alleles did not change the results (OR = 1.67, 95% CI [1.02‐2.72]). Sensitivity analyses using the 25 th percentile of plasma Aβ42 /Aβ40 ratio (≤ 0.103) as an alternative cutoff and long‐term OHYPER (at least two‐thirds of visits over 12 months) reported consistent findings. Conclusion: OHYPER was associated with lower plasma Aβ42 /Aβ40 ratio in community‐dwelling older adults, even after accounting for potential confounders. Monitoring OHYPER may have clinical utility for identifying patients who are at risk for cognitive decline, AD or in the preclinical stages of the disease.